Comparison of posturographic outcomes between two different devices. (27th March 2019) - Reinhardt, Lars; Heilmann, Florian; Teicher, Mirjam; Lauenroth, Andreas; Delank, Karl-Stefan; Schwesig, René; Wollny, Rainer; Kurz, Eduard
Abstract: The Interactive Balance System (IBS), a posturography device for assessing posture control, is widely used in clinical and rehabilitation settings. However, data on the validity of the device are unavailable. Fluctuations of the center of pressure (COP) were measured in 24 healthy participants (age: 29 ± 5 (mean ± SD) years, 12 females) synchronously using the IBS, which was rigidly mounted on a Kistler platform. Four different bipedal conditions were examined: eyes open or closed on stable or soft surfaces. Time series were compared using congruity ( CON, proportion of the measurement time during which values of both devices changed similarly in direction), whereas IBS-specific postural outcomes were correlated with traditional postural control outcomes of the Kistler force platform. The time-displacement curves showed similar shapes for CON (>0.9) for each of the four standing conditions without differences between male and female participants ( P > 0.39). The path length results of both devices showed very high linear associations, explaining on average 92% (medio-lateral) or 96% (anterior-posterior) of the common variance. The Kistler path length of the anterior-posterior direction revealed nearly perfect linear associations with the stability index of the IBS ( r 2 > 0.99). The results of this study indicate that the IBS provides valid posturographic results. Since the medial-lateral and anterior-posterior trajectories of the IBS can be used to calculate COP fluctuations, comparisons between different measurement systems are possible.